2018
DOI: 10.1002/eat.22897
|View full text |Cite
|
Sign up to set email alerts
|

Rates of abstinence following psychological or behavioral treatments for binge‐eating disorder: Meta‐analysis

Abstract: The present findings demonstrate that 50% of patients with BED do not fully respond to treatment. Continued efforts toward improving eating disorder treatments are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
102
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 79 publications
9
102
0
2
Order By: Relevance
“…The first was that these abstinence estimates in clinically representative studies were similar to those reported in recent meta‐analyses of efficacy studies. More specifically, our post‐treatment estimates calculated for BN and BED patients were comparable to the post‐treatment estimates calculated in RCTs of CBT for BN (Linardon & Wade, ) and BED (Linardon, ). The second finding was that we found no significant relationship between the degree of clinical representativeness of included studies and the overall abstinence estimates, although we did find preliminary that certain characteristics (e.g., licensed therapists vs. research therapist) may be associated with smaller effects.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The first was that these abstinence estimates in clinically representative studies were similar to those reported in recent meta‐analyses of efficacy studies. More specifically, our post‐treatment estimates calculated for BN and BED patients were comparable to the post‐treatment estimates calculated in RCTs of CBT for BN (Linardon & Wade, ) and BED (Linardon, ). The second finding was that we found no significant relationship between the degree of clinical representativeness of included studies and the overall abstinence estimates, although we did find preliminary that certain characteristics (e.g., licensed therapists vs. research therapist) may be associated with smaller effects.…”
Section: Discussionsupporting
confidence: 79%
“…For example, some reported outcomes only related to binge‐purge frequencies, others reported outcomes reflecting global scores on several disparate measurement tools (e.g., Eating Disorder Examination and Eating Attitudes Test), yet some only reported outcomes related to specific symptom subscales (e.g., shape and weight concerns). Thus, pooling many operationally distinct outcomes together into a summary effect would have not only prevented us from directly comparing our findings with those from previously reported meta‐analyses of RCTs (Linardon, ; Linardon & Wade, ), but would have also offered little clinically relevant information. Consequently, conducting a meta‐analysis solely on abstinence rates was most appropriate for our aims.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health promotion programs may complement school‐based DE prevention programs such as Bodythink (Eating Disorders Association & Faberge Lever, ), “Happy Being Me” (Richardson & Paxton, ) and “The Body Project” (Stice, Butryn, Rohde, Shaw, & Marti, ); programs that aim to reduce current or future eating pathology and promote body confidence. Promotion and prevention programs are all the more important in light of recent research which highlights that even evidence‐based treatments for eating disorders yield disappointing results (Linardon, ; Linardon & Wade, ).…”
Section: Discussionmentioning
confidence: 99%